THE PROTESTAND DISTRIBUTION: THE CASES OF "FEMEN" AND "PUSSY RIOT" - MAŽEIKIS, GINTAUTAS (Politologija, 2013)
The article draws on the interrelations of manifestation, representation, and distribution on the basis of historical examples, cases of “Femen” and “Pussy Riot”, and the analysis of actions of the art groups “Voina” and “Zmena”. The paper maintains that contemporary persuasion is based on the political economy of images rather than on the semiotics and psychoanalysis of images. The creation, reproduction, and distribution of popular images as well as political ones depends more on the market needs and art/science of marketing than on power and representation. Monopolies and corporations of the media could dictate the content of representations and define consumption in the period of analogous paper media, as G. Debord wrote about it. However, multichannel and self-organising informational networks are based not on the dictat of the propaganda or commercial spectacle, but on the semi-free social distributions and creative consumption. Besides, the contemporary semantic value and the significance of public icons depend equally on the form and process of dissemination as well as on the artistic, original content. This means that the circulation of images and the accumulation of symbolical and, as a consequence, financial capital doesn’t necessarily demand a special artistic value or developed aesthetic characteristics. Diminishing of artistry and targeting of protest actions in order to satisfy the desire of consumers are combined with both civic and commercial objectives. The synergy of civic and consumer interests, political activism and consumption in the media characterizes the contemporary political consciousness. Deterioration of art to the elementary street or labour art, adjustment of visuality in order to supply policy requirements and social networking needs blends with the growth of influence of digital technologies, the social and commercial distribution of reportages. The desire to watch the inspirational art as well as the political visions is supported and satisfied by the production and reproduction of special political events. The article considers two cases: the Ukrainian semi-commercial movement “Femen” and non-commercial art activists as well as the punck rock band „Pussy Riot“ as two possible tactics in the contemporary protest movement. The aim of the article is to analyse various possibilities for protest art tactics in the contemporary media. The social movement “Femen”, its sexism and declarative feminism, its conspicuous activism are an example of manufacturing protest events for political and commercial purposes, for consolidating the interests of corporative capital and civic society. On the contrary, “Pussy Riot” demonstrates manifestations independent of the corporative capital. They are very anarchistic and develop the protest street art. However, the problems of the distribution of art production involved the band into an active participation in the social media and into the creation of independent, communal circles of the circulation of images. Intentions of civic-consumer consciousness directly depend on the content of messages, artistic images and the possible euphoria affects that were disseminated in the digital internet spaces. It is the reason to re-evaluate the interrelations among their manifestation, representation, and distribution in the contemporary social media. The contemporary market oriented to the distribution dictates the demands for the reproduction of representations as also in the new media. If the propaganda is based only on the mass production of messages, its information is ineffective and doesn’t correspond on the logic of the contemporary market research and control, on the process of visuality consumption. The stories about the popularization of the art groups “Voina”, “Zmena” and especially “Pussy Riot” are examples of a well organized artistic protest in the political field and on the political arena with a different dependence on commercial corporations. Their activities cover the spheres of artistic manifestations, the digital market of the distribution and production of consumers’ desires and euphoria. The distribution of protest art goes on in the civic political field, and the growth of the protest movement means the development of demands for protest art production. Creative and informational industries seek to delay mass euphoria and then to keep it in order to exploit the enthusiasm and energy of masses for commercial purposes. The purpose of visible and invisible industries is the accumulation of various forms of capital, but not specific moral or political ideals. Critical thinking and political leadership correspond to different narratives of visual scene and the logic of the mass distribution of the visible. Critical thinking and political leadership need artistic experiments in the streets and in the media as models for political behaviour and demands. Artistic examples help to create the diversity of political manifestations and representations, the multiplicity of the political field. The Ukrainian, Russian, Belorussian modern political protests use different tactics from semi-conformism with the official power up to the antagonistic negation of the government, from the semi-commercial “Femen” and its collaboration with the corporate media up to the completely autonomous and anarchistic “Pussy Riot”. I think that all forms of artistic activism are acceptable for the development of free civic society, but they demand a critical perception and development.